Ethanol infusion into the vein of Marshall for recurrent perimitral atrial tachycardia after catheter ablation for persistent atrial fibrillation. Issue 5 (8th September 2020) - Sang, Caihua; Lai, Yiwei; Long, Deyong; Li, Mengmeng; Bai, Rong; Jiang, Chenxi; Wang, Wei; Li, Songnan; Tang, Ribo; Guo, Xueyuan; Liu, Nian; Zhao, Xin; et al.
Abstract: Background: Catheter ablation of perimitral atrial tachycardia (PMAT) is challenging. Epicardial conduction of the Marshall bundle (MB) across the mitral isthmus (MI) remains an important cause of recurrent tachycardia. The role of ethanol infusion into the vein of Marshall (EI‐VOM) for PMAT has not been fully elucidated. Methods: The study enrolled 28 consecutive patients with recurrent PMAT after atrial fibrillation (AF) ablation. Conventional PMAT (group 1, n = 15) and MB‐related PMAT (group 2, n = 13) were diagnosed by detailed activation mapping and entrainment mapping. VOM venography and EI‐VOM were first performed, and additional ablation was performed if necessary. Results: The VOM was accessible in 24 (85.7%) patients (12 [80%] in group 1 and 12 [92.3%] in group 2). Patients with MB‐related PMAT were more responsive to EI‐VOM (as shown by PMAT termination or tachycardia cycle length prolongation) (92.4% vs 53.3%, P = .038). In the 16 patients requiring additional ablation after EI‐VOM, all residual MI conduction gaps were located on the annular side of the MI. At the end of the procedure, MI bidirectional block was achieved in 14 (93.3%) patients in group 1 and in 12 (92.3%) patients in group 2 ( P = 1.000). After a mean follow‐up of 7.5 ± 3.1 months, three (10.7%) patients had recurrent AT. Conclusions: EI‐VOM is feasible and effective in the treatment of PMAT after AF ablation, especially in patients with MB‐related PMAT.